Stereocilia-staircase spacing is influenced by myosin III motors and their cargos espin-1 and espin-like - Seham Ebrahim (Nature Portfolio, 2016)
Stereocilia of the inner ear have graded heights that are thought to be regulated by the myosin-III family members MYO3A and MYO3B. Here the authors identify espin-1 and espin-like (ESPNL) as cargo that differentially influence the functions of both motors to regulate stereocilia length.